2016
DOI: 10.18632/oncotarget.12562
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis inducing factor (AIF) mediates lethal redox stress induced by menadione

Abstract: Mitochondrial apoptosis inducing factor (AIF) is a redox-active enzyme that participates to the biogenesis/maintenance of complex I of the respiratory chain, yet also contributes to catabolic reactions in the context of regulated cell death when AIF translocates to the cytosol and to the nucleus. Here we explore the contribution of AIF to cell death induced by menadione (2-methyl-1,4-naphtoquinone; also called vitamin K3) in conditions in which this pro-oxidant does not cause the mitochondrial release of AIF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
1
16
0
4
Order By: Relevance
“…This situation revealed that AIF tends to modulate arylation capacity of menadione and GSH rather than acts as NADH:quinonereductase. It confirmed that the lethal action of AIF is not related to its oxidoreductase activity 8,10,11,14 . Further investigation on AIF-thiodione revealed that AIF tends to interact with thiodione compare to menadione or GSH.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…This situation revealed that AIF tends to modulate arylation capacity of menadione and GSH rather than acts as NADH:quinonereductase. It confirmed that the lethal action of AIF is not related to its oxidoreductase activity 8,10,11,14 . Further investigation on AIF-thiodione revealed that AIF tends to interact with thiodione compare to menadione or GSH.…”
Section: Discussionmentioning
confidence: 54%
“…As mention above that arylation capacity of menadione involving thiol proteins, computational study was applied to determine the affinity of arylation precursors; menadione or GSH to AIF. Given that in the modulation menadione cytotoxicity AIF does not use its nuclease activity (associated with C-terminal domain of AIF) and during that time AIF stay inside mitochondria (associated with N-terminal domain) 11 , computational approach focus on FAD and NADH domain of AIF. The result showed that affinity energy of AIF-menadione on NADH domain -6.9 kcal/mol, it is higher than AIF-menadione on FAD domain that showed -7.3 kcal/mol.…”
Section: Binding Energy Analysis Of Menadione or Gsh On Fad Domain Ofmentioning
confidence: 99%
See 3 more Smart Citations